Self‐Reported Questionnaire Detects Family History of Cancer in a Pancreatic Cancer Screening Program. Issue 4 (30th December 2016) - Lucas, Aimee L.; Tarlecki, Adam; Van Beck, Kellie; Lipton, Casey; RoyChoudhury, Arindam; Levinson, Elana; Kumar, Sheila; Chung, Wendy K.; Frucht, Harold; Genkinger, Jeanine M.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer death; approximately 5–10% of PDAC is hereditary. Self‐administered health history questionnaires (HHQs) may provide a low‐cost method to detail family history (FH) of malignancy. Pancreas Center patients were asked to enroll in a registry; 149 with PDAC completed a HHQ which included FH data. Patients with FH of PDAC, or concern for inherited PDAC syndrome, were separately evaluated in a Prevention Program and additionally met with a genetic counselor (GC) to assess PDAC risk ( n  = 61). FH obtained through GC and HHQ were compared using Wilcoxon signed‐rank sum and generalized linear mixed models with Poisson distribution. Agreement between GC and HHQ risk‐assessment was assessed using kappa (κ) statistic. In the Prevention Program, HHQ was as precise in detecting FH of cancer as the GC (all p  > 0.05). GC and HHQ demonstrated substantial agreement in risk‐stratification of the Prevention Program cohort (κ = 0.73, 95% CI 0.59–0.87.) The sensitivity of the HHQ to detect a patient at elevated risk (i.e., moderate‐ or high‐risk) of PDAC, compared to GC, was 82.9% (95% CI 67.3–92.3%) with a specificity of 95% (95% CI 73.1–99.7%). However, seven patients who were classified as average‐risk by the HHQ were found to be at an elevated‐risk of PDAC by the GC. In the PDAC cohort, 30/149 (20.1%) reported at least one first‐degree relative (FDR) with PDAC. The limited sensitivity of the HHQ to detect patients at elevated risk of PDAC in the Prevention Program cohort suggests that a GC adds value in risk‐assessment in this population. The HHQ may offer an opportunity to identify high‐risk patients in a PDAC population.